Based on the Development and Verification of a Risk Stratification Nomogram: Predicting the Risk of Lung Cancer-Specific Mortality in Stage IIIA-N2 Unresectable Large Cell Lung Neuroendocrine Cancer Compared With Lung Squamous Cell Cancer and Lung Adenocarcinoma - Yang, Ying; Shen, Cheng; Shao, Jingjing; Wang, Yilang; Wang, Gaoren; Shen, Aiguo (Frontiers in Oncology, 2022)
Background: The purpose of this study is to predict overall survival (OS) and lung cancer-specific survival (LCSS) in patients with stage IIIA-N2 unresectable lung squamous cell cancer (LUSC), lung adenocarcinoma (LUAD), and large cell neuroendocrine cancer (LCNEC) by constructing nomograms and to compare risk and prognostic factors affecting survival outcomes in different histological subtypes. Methods: We included 11,505 unresectable NSCLC patients at stage IIIA-N2 between 2010 and 2015 from the Surveillance, Epidemiology and End Results (SEER) database. Besides, competition models and nomograms were developed to predict prognostic factors for OS and LCSS. Results: Analysis of the SEER database identified 11,505 NSCLC patients, of whom 5,559 (48.3%) were LUAD, 5,842 (50.8%) were LUSC, and 104 (0.9%) were LCNEC. Overall, both OS and LCSS were significantly better in stage IIIA-N2 unresectable LUAD than in LCNEC, while there was no statistically significant difference between LSCC and LCNEC. Age, gender, T-stage, chemotherapy, and radiotherapy were significantly associated with OS rates in LUAD and LUSC. However, chemotherapy was the only independent factor for LCNEC (P<0.01). From the competing risk model, we found that older age, larger tumors, and treatment with chemotherapy and radiotherapy were associated with a worsening risk of death in LUAD and LUSC. In particular, there was no difference in male patients with LCSS compared to female patients with LUSC. Unlike prognostic factors for OS, our study showed that both chemotherapy and radiotherapy were all LCNEC specific survival factors for both LCSS and non-LCSS LCNEC. CONCLUSION: Our study reports that unresectable patients with stage IIIA-N2 LCNEC and LUSC have worse lung cancer-specific survival than LUAD. The study's first prognostic nomogram constructed for patients with unresectable stage IIIA-N2 NSCLC can accurately predict the survival of different histological types, which may provide a practical tool to help clinicians assess prognosis and stratify these prognostic risks to determine which patients should be given an optimized individual treatment strategy based on histology.